The Wordsworth Dictionary Of Bible Quotations - Manser, Manser H (Wordsworth Editions Ltd, 1995)
This book provides a fresh selection of familiar and not so familiar biblical quotations. It contains over 4000 quotations from the Authorized version of the Bible.
Keywords: Dictionaries-English Language-Reference-Non fiction